2015
DOI: 10.5649/jjphcs.41.321
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Eicosapentanenoic Acid Ethyl Ester Formulations with Volatile Compound

Abstract: Eicosapentanenoic acid ethyl ester (EPA-E) formulation is a drug derived from fish oil. Some EPA-E formulations have a special odor depending on the manufacturing process and the type of sardine raw materials used. This odor affects the compliance of some patients. In this study, we report our assessment of the odors in each EPA-E formulation with gas chromatography/mass spectrometry (GC/MS). We used 3 lots of an original drug and 5 generic EPA-E formulations. EPA-E formulations were incubated at 40℃ in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These products may contain extra contaminants due to differences in the raw materials used or in the purification process. Jobu et al conducted an accelerated test using the branded and several generic versions of a highly purified EPA and found that the decomposition products from autoxidation during storage produced odors, which may influence the drug adherence [8]. This problem was significantly suppressed by preservation with nitrogen gas replacement.…”
Section: Production Step Of Epadel ®mentioning
confidence: 99%
See 1 more Smart Citation
“…These products may contain extra contaminants due to differences in the raw materials used or in the purification process. Jobu et al conducted an accelerated test using the branded and several generic versions of a highly purified EPA and found that the decomposition products from autoxidation during storage produced odors, which may influence the drug adherence [8]. This problem was significantly suppressed by preservation with nitrogen gas replacement.…”
Section: Production Step Of Epadel ®mentioning
confidence: 99%
“…EPA drugs are prescribed as branded (EPADEL ® : highly purified EPA ethyl ester) or generic products in Japan but no data exist regarding differences in the treatment outcomes between the products. Also, Jobu et al conducted an accelerated test using the branded and several generic versions of a highly purified EPA and found that the decomposition products from autoxidation during storage produced odors, which may influence the drug adherence [8]. Therefore, we investigated the differences in EPA, DHA, AA and the EPA/AA ratio through blood sampling six months after daily administration of EPADEL ® and a generic EPA product (released by a drug company) was initiated in patients with cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%